Technology pedagogy content knowledge framework to prepare Indonesian career counselors - Zikra Zikra; Miftahul Fikri; Afdal Afdal; Indah Sukmawati; Tjung Hauw Sin; Nurhastuti Nurhastuti; Suryanef Suryanef (International Journal of Evaluation and Research in Education (IJERE), 2024)
Technological pedagogical and content knowledge (TPACK) is one of the smart solutions for implementing learning in accordance with the demands of education by integrating technology. The purpose of the study was to analyze the competency level of counselors in Indonesia in terms of age in terms of age, gender, and level of education. The research design used a cross-sectional survey in a non-experimental quantitative study. Respondents in this study amounted to 420 counselors in Indonesia obtained by using a proportional random sampling technique. Data were collected by questionnaire technological pedagogy content knowledge test for counselors (TPACK-TFC). The results of the study found that the TPACK was owned by counselors with an average score of 46.78 in the low category. Judging from the aspect of technology knowledge (TK), a score of 59.88 was obtained in the medium category, content knowledge (CK), pedagogical knowledge (PK), pedagogical content knowledge (PCK), technological content knowledge (TCK), technological pedagogical knowledge (TPK) was at a relatively low level. The results showed that Indonesian counselors have not fully integrated learning models using aspects namely technology, pedagogy, and content, and need to get attention from the government, higher education institutions, and the community for the development of quality guidance and counseling services and counselor careers in the future.